Topical treatment of acyclovir-resistant herpes simplex virus stomatitis after allogeneic hematopoietic cell transplantation - Heidenreich, Daniela; Kreil, Sebastian; Müller, Nadine Zoé; Jawhar, Mohamad; Nolte, Florian; Hofmann, Wolf-Karsten; Klein, Stefan (Oncology research and treatment, 2020)
Introduction: We report on patients who developed severe acyclovir-resistant (ACVr) herpes simplex virus 1 (HSV-1) stomatitis after allogeneic hematopoietic cell transplantation (HCT). Patients: HCT patients suffering from HSV-1 stomatitis without response after 1 week of high-dose acyclovir (ACV) were tested for ACV resistance. Patients with proven ACV resistance were treated either topically with cidofovir solution and gel or with topical foscavir cream or with intravenous foscavir. Results: Among 214 consecutive HCT patients, 6 developed severe ACVr HSV-1 stomatitis (WHO grade III n = 1, WHO grade IV n = 5). All 6 patients suffered from relapse of acute myeloid leukemia (AML) after HCT. ACVr stomatitis was treated topically with first-line (n = 4) or second-line (n = 2) cidofovir. Topical foscavir cream was applied as first-line (n = 1) or second-line (n = 1) therapy. Intravenous foscavir was used in 3 patients (first-line therapy, n = 1; second-line therapy, n = 2). Complete remission was reached by topical cidofovir (n = 3), topical foscavir (n = 1), and intravenous foscavir (n = 1), respectively. Five of the 6 patients died due to progression of leukemia. Only 1 patient survived. Conclusions: ACVr HSV-1 stomatitis is a severe complication in AML patients relapsing after HCT. It reflects the seriously impaired general condition of these patients. This analysis shows that topical treatment with cidofovir or foscavir might be a sufficient first-line therapy approach in ACVr HSV-1 stomatitis. It might serve as a less toxic alternative to intravenous foscavir.
Gesehen am 01.10.2024